Factors Affecting Sharia Insurance Acceptance Among the Community in Mandailing Natal - Sandi Nugraha; Muhammad Ikhsan Harahap; Tri Inda Fadhila Rahma (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Sharia insurance is a type of financial safeguard that adheres to Islamic principles. Despite Mandailing Natal Regency having a significant Muslim demographic and various Islamic financial entities, there is still a relatively modest interest in sharia insurance among the populace. This research aims to analyze how religion and knowledge of Islamic finance influence the acceptance of sharia insurance within the community of Mandailing Natal Regency. The study employs a quantitative approach, utilizing purposive sampling with 100 participants. For data evaluation, techniques such as validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and determination coefficient are conducted using SPSS software. The study's results indicate that both religiosity and Islamic financial literacy considerably and positively affect the acceptance of sharia insurance, both independently and collectively. Additionally, the impact of Islamic financial literacy is shown to be greater than that of religiosity, suggesting that comprehension of sharia insurance's concepts, agreements, advantages, and processes is crucial for enhancing public acceptance. These findings imply that enhancing education and literacy regarding Islamic finance should be prioritized by insurance companies, Islamic financial institutions, and local authorities to promote greater acceptance of Islamic insurance offerings.